1999
DOI: 10.1159/000014090
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Modulates Cellular Proliferation in Developing Human Jejunum and Colon

Abstract: Several lines of evidence suggest an important role for insulin in the regulatory mechanism of rodent small intestinal development. To investigate its potential implication in human gut, the immunofluorescent localization of insulin receptors (IR) and the influence of insulin (30 µU or 3 mU/ml) on [3H]-thymidine incorporation and on lactase and alkaline phosphatase activities were studied in fetal jejunum and colon (14–19 weeks). We demonstrate the early presence of IR, mainly detected in the basola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Human intestinal explants32 have been used for a variety of studies including the study of intestinal lipid transport,33 the effect of insulin on epithelial cell proliferation,34 and the synthesis of brush border membrane proteins 35. Explants offer the opportunity to study epithelial cell biology in the context of normal tissue components and organization.…”
Section: Discussionmentioning
confidence: 99%
“…Human intestinal explants32 have been used for a variety of studies including the study of intestinal lipid transport,33 the effect of insulin on epithelial cell proliferation,34 and the synthesis of brush border membrane proteins 35. Explants offer the opportunity to study epithelial cell biology in the context of normal tissue components and organization.…”
Section: Discussionmentioning
confidence: 99%
“…Signals derived from luminal amniotic fluid may also contribute to the development of enzyme activities in utero (44), possibly mediated by specific growth factors. Organ culture studies of human fetal intestine in defined tissue culture medium have demonstrated differential effects of hydrocortisone, insulin, and epidermal growth factor in regulating hydrolase expression, apolipoprotein and lipoprotein secretion, and cellular proliferation (45)(46)(47)(48)(49). However, the implication of these important findings to tissue development in utero are somewhat limited by the current inability to perform long-term in vitro experiments on late-gestational fetal intestine.…”
Section: Discussionmentioning
confidence: 99%
“…During the postnatal period insulin-like growth factor (IGF)-I becomes more important than IGF-II (Breier et al 2000, Butler & LeRoith 2001. The somatotropic axis and especially IGFs, besides insulin, is involved in GIT development and especially in proliferation and maturation of enterocytes (Laburthe et al 1988, Schober et al 1990, Odle et al 1996, MacDonald 1999, Menard et al 1999. It has been demonstrated that IGF-II and insulin are involved in the mechanisms governing the differentiation of intestinal epithelium while IGF-I is mostly associated with crypt cell proliferation (Jehle et al 1999).…”
Section: Introductionmentioning
confidence: 99%